2016
DOI: 10.3389/fmicb.2016.01207
|View full text |Cite
|
Sign up to set email alerts
|

Wheat and Rice Growth Stages and Fertilization Regimes Alter Soil Bacterial Community Structure, But Not Diversity

Abstract: Maintaining soil fertility and the microbial communities that determine fertility is critical to sustainable agricultural strategies, and the use of different organic fertilizer (OF) regimes represents an important practice in attempts to preserve soil quality. However, little is known about the dynamic response of bacterial communities to fertilization regimes across crop growth stages. In this study, we examined microbial community structure and diversity across eight representative growth stages of wheat-ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(49 citation statements)
references
References 62 publications
6
39
0
Order By: Relevance
“…Microbial diversity is a fundamental property of soil ecosystems as microorganisms play critical roles in nutrient cycling, soil structure maintenance, and crop production (Madigan, Martinko, Dunlap, & Clark, ). Although bacterial diversity is critical for the maintenance of soil health and quality (Garbeva, van Veen, & van Elsas, ), uncertainties still remain across the literature regarding the long‐term effect of N fertilization on bacterial diversity, e.g., negative effects (Ling et al., ; Niu et al., ; Zhou et al., ) and no/positive effects (Ramirez et al., ; Wang et al., ; Yuan et al., ). These results can probably be attributed to the great heterogeneity in soil properties, rate of fertilization, water management regimes, and other biotic and abiotic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Microbial diversity is a fundamental property of soil ecosystems as microorganisms play critical roles in nutrient cycling, soil structure maintenance, and crop production (Madigan, Martinko, Dunlap, & Clark, ). Although bacterial diversity is critical for the maintenance of soil health and quality (Garbeva, van Veen, & van Elsas, ), uncertainties still remain across the literature regarding the long‐term effect of N fertilization on bacterial diversity, e.g., negative effects (Ling et al., ; Niu et al., ; Zhou et al., ) and no/positive effects (Ramirez et al., ; Wang et al., ; Yuan et al., ). These results can probably be attributed to the great heterogeneity in soil properties, rate of fertilization, water management regimes, and other biotic and abiotic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Mineral, in contrast to organic, inputs alter the general balance of soil stoichiometry, thereby resulting in adaptative selection of a resident population of oligotrophic taxa (high C use efficiency, slow growing) instead of more copiotrophic taxa (low C use efficiency, fast growing). Wang et al (41) reported that the application of organic fertilizers increased the abundance of generally copiotrophic bacterial groups, while application of mineral fertilizers increased the abundance of oligotrophic groups. Thus, we hypothesized that there will be a shift in dominance and response strategies of specific microbial groups involved in residue assimilation in soils after manuring compared to these strategies after only mineral fertilization.…”
mentioning
confidence: 99%
“…The soil root zone, especially the rhizosphere, is the active zone of microbial and root activity (Lagos et al 2015). The pH of the rhizosphere zone is, therefore, critical in deciding microbial activity (Wang et al 2016), which in turn regulates the innumerable chemical reactions involved in nutrient transformations and uptake by plant roots. The ideal pH range for active growth and development of plants and microbes is 6.5-7.5.…”
Section: Resultsmentioning
confidence: 99%